Сложные прилагательные с причастием II в качестве второго компонента в английском языке - Венгерова, С. (Kalbotyra, 1976)
The patterns of compound adjectives containing Participle II as their second component are; n Part II, a Part II, adv Part II. According to the syntactic relations in the corresponding phrases these compounds are classified into: 1. compounds with objective relations (frost-sharpened, oilcloth-covered), 2. compounds with adverbial relations (factorymode, long-faded), 3. compounds with subjective relations (heartstricken, neckwrung), 4. compounds with predicative relations (slave-born, green-painted). Certain criteria are established helping to distinguish compound words from phrases in marginal cases. The material investigated has shown that the patterns analysed are most productive in the following cases: 1. n Part II with n denoting agent or material; 2. a Part II denoting quality or state which is the result of the action expressed by the participle; 3. adv Part II containing the stem of an adverb of manner homonymous with an adjective (most often-, long-, short-, high-, low, deep-, wide-, clear, hard-, new, and also well-). The same participles are usually met in various compounds formed according to one and the same or different patterns. New compounds are freely formed with the most frequently occurring components of the already existing compound words.